The relationship of laboratory values with prognosis in acute stroke recanalization treatment applied patients - Acır, İbrahim; Erdoğan, Hacı Ali; Olgun Yazar, Hülya; Suskun, Melis; Yayla, Vildan (The European Research Journal, 2023)
Objectives: Many factors affect the results of acute recanalization treatment and prognosis of ischemic stroke patients. Some markers which has a role in inflammation process cause atherosclerosis that leads to ischemic stroke. We aimed to evaluate the relationship between admission laboratory findings and prognosis in patients to whom acute recanalization therapy were applied. Methods: In our study, we evaluated 139 acute stroke patients to whom acute recanalization therapies had been applied. Demographic data, glomerular filtration rate, uric acid, albumin, lipid profile, C-reactive protein, fibrinogen values were evaluated. Admission and discharge National Institutes of Health Stroke Scale and modified Rankin Scale scores were recorded. The effect of laboratory parameters on prognosis was examined. P